Impact of early reoperation on graft survival after liver transplantation: Univariate and multivariate analysis. Issue 6 (28th May 2018) - Elsabbagh, Ahmed M.; Girlanda, Raffaele; Hawksworth, Jason; Pichert, Matthew D.; Williams, Cassie; Pozzi, Agostino; Kroemer, Alexander; Nookala, Anupama; Smith, Coleman; Matsumoto, Cal S.; Fishbein, Thomas M.
Abstract: Background: Data on rate, risk factors, and consequences of early reoperation after liver transplantation are still limited. Study design: Single‐center retrospective analysis of data of 428 patients, who underwent liver transplantation in period between January 2009 and December 2014. Univariate and multivariate analysis were used to study the risk factors of early reoperation and its impact on graft survival. Results: Of 428 patients, 74 (17.3%) underwent early reoperation. Of them, 46 (62.2%) underwent reoperation within the first week and 28 (37.8%) underwent reoperation later than 1 week after transplantation. With multivariate analysis, significant risk factors of early reoperation included pretransplant ICU admission, previous abdominal surgery and diabetes. Early reoperation itself was not found to be an independent predictor of graft loss. However, early reoperation later than 7 days from transplant was found to be independent predictor of graft loss (odds ratio [OR] = 5.125; 95% CI, 1.358‐19.552; P = .016). In our series, other independent predictors of graft loss were MELD score ( P = .010) and operative time ( P = .048). Conclusions: This analysis demonstrates that early reoperations later than a week appear to negatively impact the graft survival. The timing of early reoperation should be a focus of additional studies.